Sandwich Core Material Development for Ship Deck Structure - Zubaydi, A.; Budipriyanto, A.; Iswidodo, W. (Institut Teknologi Sepuluh Nopember, 2017)
Development of sandwich materials for ship structure is aimed mainly to reduce the ship light weight so that the ship payload increases. This paper addresses development of sandwich core material suitable for ship structure. The core materials were composed of synthetic resin and talc; percentages of talc by total weight investigated were 10%, 20%, 30%, and 40%. Laboratory tests stipulated by the Lloyd’s Register (LR) and Det Norske Veritas (DNV) were performed on the core materials. Moreover, sandwich plates consisted of steel faceplates and the core materials were tested using ASTM standards including tension, shear, and flexure tests. The sandwich plates were applied for designing car deck of a ro-ro ship. Analysis of the sandwich deck under design load utilizing finite element approach was carried out to select the best sandwich core materials developed in this study. It was observed that the sandwich panel deck composed of synthetic resin and core material with 40% talc was better than the others.